Comparative evaluation of mouse bone marrow mesenchymal stromal cells characteristics cultured in two different supplemented media - Kwan, Liang Lye; Nordin, Norshariza; Vidyadaran, Sharmili; Niu, Jin Tan; Mohd Rawi, Rohayu Izanwati; Thilakavathy, Karuppiah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2022)
Introduction: Preclinical studies on mesenchymal stromal cells (MSC) have allowed the cells to be considered as a promising candidate for cellular therapy. In recent years, conflicting data have been reported regarding various aspects of their characteristics, development and differentiation potential, which may be due to arrange of factors. Among the factors worth investigating is the culture medium formulation. Methods: Here we have made a comparative characterization of mouse bone marrow mesenchymal stromal cells (mBM-MSC) that were cultured using two common supplements, MesenCult™ Stimulatory Supplement (MSS) and fetal bovine serum (FBS), under the same experimental conditions at different passages. Clonogenic potential, cumulative population doubling level (CPDL), population doubling time (PDT), immunophenotyping, differentiation, immunosuppression potentials and chromosome analysis of early and late passages mBM-MSC were assessed. Results: Our findings showed that the CPDL, immunophenotype and immunosuppression potential of mBM-MSC were similar. However, variations were seen in their clonogenicity, population doubling time and differentiation efficacy whereby all of these were enhanced in DMSS. These observations suggest that their genetic make-up may be affected by both supplements upon prolonged culture. Interestingly, this conjecture was supported when chromosomal analysis revealed genetic instability of mBM-MSCs cultured in both supplements. Conclusion: In conclusion, culture medium formulation was shown to cause variations and spontaneous transformation in mBM-MSCs raising concerns on the usage of late passages mBMMSCs in fundamental and preclinical downstream experiments.